2000
DOI: 10.1021/la991109r
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Aminodextran−CdS Nanoparticle Complexes and Biologically Active Antibody−Aminodextran−CdS Nanoparticle Conjugates

Abstract: Stable aqueous dispersions consisting of CdS nanoparticles having modal diameters, ranging between 2 and 8 nm, were prepared with amino-derivatized polysaccharides (aminodextrans, hence abbreviated as Amdex) as the stabilizing agents. The size, stability, and luminescence intensity of such dispersions were shown to be dependent on the types of the cadmium salts and aminodextrans used, as well as on the reactant concentrations. Specifically, it was demonstrated that the degree of substitution of amino groups in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 64 publications
0
62
0
Order By: Relevance
“…39 Alternatively, turbulence-based mixing of various solvents with supercritical fluid enhanced by an ultrasound field has been used to precipitate protein, 40 and drug, 41 nanoparticles of controlled size and distribution. Continuous flow microfluidic methods for synthesis of nanoparticles have also appeared in literature.…”
Section: Resultsmentioning
confidence: 99%
“…39 Alternatively, turbulence-based mixing of various solvents with supercritical fluid enhanced by an ultrasound field has been used to precipitate protein, 40 and drug, 41 nanoparticles of controlled size and distribution. Continuous flow microfluidic methods for synthesis of nanoparticles have also appeared in literature.…”
Section: Resultsmentioning
confidence: 99%
“…Since the use of ligand-conjugated QDs as fluorescent biolabeling reagents was reported in 1998 by the groups of Alivisatos [51] and Nie [52], many approaches to QD applications have been realized in the bioanalytical field such as DNA sequencing, tissue immune-diagnostics and single molecular imaging [53][54][55][56][57][58][59][60][61][62][63][64][65][66]. The advantages of QDs as biolabeling agents are (i) tunability of the emission wavelength by changing the particle size, (ii) a sharp and symmetrical emission peak, (iii) the high intensity and long lifetime of the fluorescence and (iv) a wide range of excitation wavelengths.…”
Section: Preparation Of Cds Quantum Dots By Co-precipitation In the Pmentioning
confidence: 99%
“…There is a need to develop more safe and cost-effective biocidal materials. Nanosized particles either simple or composite by nature, exhibit unique physical and chemical properties and shows a potential of being used in various biomedical applications [7,8].Studies on graphene and graphene-based materials has found their use in medicine and life sciences which includes imaging [9], biosensors [10,11], drug delivery [12][13][14] and pathogen control [15,16]. The response of using graphene oxide on microorganisms has been studied extensively.…”
mentioning
confidence: 99%